Analisis Penerapan PSAK407 Tentang Akuntansi Ijarah Pada Gadai Emas di Bank BJBS yariah KCP Kopo - Dina Ecky Saputri; Mia Lasmi Wardiyah (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Bank BJB Syariah, Kopo Sub-Branch Office, is a sharia financial institution that offers Gold Pawn (Gadai Emas) as one of its financing products, using gold as collateral. In practice, this product applies the rahn contract as the basis for collateral provision, accompanied by an ijarah contract for safekeeping and maintenance fees. With the growing public interest in this product, proper monitoring and evaluation of sharia accounting standards implementation is essential. This study aims to evaluate the implementation of PSAK 407 on Ijarah Accounting in the context of Gold Pawn financing, covering aspects of recognition, measurement, presentation, and disclosure. A descriptive qualitative method was used, with data collected through interviews with Back Office staff and financing analysts at Bank BJB Syariah Kopo Sub-Branch, as well as literature review. The findings indicate that the implementation of the Gold Pawn mechanism complies with DSN-MUI Fatwa No. 26/DSN-MUI/III/2002 on gold rahn, and in general, the application of PSAK 407 has been well implemented. These findings are expected to serve as a reference to improve sharia gold pawn accounting practices and support a more transparent and accountable Islamic financial ecosystem.